Aggregate Unemployment Decreases Individual Returns to Education - Andreas Ammermüller; Anja Kuckulenz; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
On the basis of a theoretical model, we argue that higher aggregate unemployment affects individual returns to education. We therefore include aggregate unemployment and an interaction term between unemployment and the individual education level in a standard Mincer equation. Our results show that an increase in regional unemployment by 1% decreases the returns to education by 0.005 percentage points. This implies that higher skilled employees are better sheltered from labour market changes with respect to their jobs but encounter larger wage changes than less skilled employees. Differences in regional unemployment can in addition almost fully explain the observed large differences in regional returns to education. We use representative individual data and regional panel variation in unemployment between different German regions and for different employee groups. We demonstrate that our results are robust with respect to aggregation bias, time lags and potential endogeneity of the unemployment variable.
Keywords: J24; C23; 330; returns to education; unemployment; regional variation; Bildungsertrag; Regionale Arbeitslosigkeit; Arbeitslosigkeit; Regionale Lohnstruktur; Schätzung; Deutschland